VICE PRESIDENT TASKS AND AUTHORITIES IN THE CONSTITUTIONAL SYSTEM OF THE REPUBLIC OF INDONESIA UNDER 1945 CONSTITUTION - Melan Yusuf Nomleni (Faculty of Law, Universitas Jenderal Soedirman, 2016)
The amendment of Constitution has not met the the life of the nation’s demand, one of which is the of the tasks and authorities of the Vice President. This sparks multiple interpretations on the role and its legal implications toward the responsibility over the Vice President tasks and. The results show several reasons underlying obscurity of the tasks and authorities regulation of the Indonesian Vice President stated in 1945 Constitution, among which is the Indonesian governance. The obscure regulation of the Vice President tasks and authorities affects on his/her responsibility. Hence, the clear regulation related to the tasks and authorities of the Vice President as President Assistant in performing state governance is required.Keywords : Regulation, Vice President, Authorities